THE IMPACT OF EXPERIENTIAL MARKETING ON CUSTOMER LOYALTY AT R-ZONE CAFÉ - Sumilat, Kezia Rahel Natasha; S. L. H. V. Joyce Lapian; Merinda H. C. Pandowo (Universitas Sam Ratulangi, 2024)
In winning business competition, a marketer must have a competitive advantage or differentiator in order to continue to survive on the products they offer. Researcher conducted this research through Qualitative methods by In-depth Interview to find out how the 5 aspects of Experiential Marketing impacted the Loyalty of Customers at R-Zone Café. The sample size of this study was 20 informants who visit R-Zone Café. Informants are female and male with range age of 17-35. The result in this study indicates that out of 5 aspects of experiential marketing Sense, Feel, Think, and Relate have the most impact for the customer to make repurchase. All 5 aspects of experiential marketing also have positive impact for the customers to being committed to the brand and have positive impact for the customer to recommend the café. Keyword: Experiential Marketing, Customer Loyalty